2015
DOI: 10.1111/dme.12727
|View full text |Cite
|
Sign up to set email alerts
|

Progression of diabetic retinopathy after bariatric surgery

Abstract: A higher pre-operative diabetic retinopathy grade, and a large decrease in HbA1c post surgery warrant closer monitoring of diabetic retinopathy after bariatric surgery. Further prospective, randomized studies are required to investigate the gender and ethnic differences found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 22 publications
1
58
2
1
Order By: Relevance
“…Whether individuals with obesity and Type 2 diabetes obtaining diabetes remission after bariatric surgery should continue retinopathy screening has been discussed previously . In our data, only one person in the RYGB group with remission demonstrated deterioration at 6‐year follow‐up, however, in this group no one suffered from previously laser‐treated retinopathy, a feature that might be important when assessing the risk of deterioration . It seems reasonable to continue ophthalmologic screenings, while waiting for stronger data.…”
Section: Discussionmentioning
confidence: 54%
“…Whether individuals with obesity and Type 2 diabetes obtaining diabetes remission after bariatric surgery should continue retinopathy screening has been discussed previously . In our data, only one person in the RYGB group with remission demonstrated deterioration at 6‐year follow‐up, however, in this group no one suffered from previously laser‐treated retinopathy, a feature that might be important when assessing the risk of deterioration . It seems reasonable to continue ophthalmologic screenings, while waiting for stronger data.…”
Section: Discussionmentioning
confidence: 54%
“…Existing data support positive, neutral and negative effects of bariatric surgery on DR . The potential risk factors for DR progression following bariatric surgery may include pre‐operation DR severity, magnitude of post‐surgery HbA1c reduction and, in some cases, gender and ethnicity …”
Section: Early Worsening Following Bariatric Surgerymentioning
confidence: 99%
“…A pilot study in patients with type 2 diabetes and morbid obesity showed that moderate background DR, or worse, increased the risk of DR progression, while minimal DR or the absence of DR resulted in a low incidence of new‐onset DR and DR progression . Findings from a retrospective, observational study in patients with type 2 diabetes showed that the probability of DR progression, to moderate or higher severity, after bariatric surgery was associated with the magnitude of HbA1c reduction from pre‐surgery levels, with a short duration of post‐operative retinal screening, with severe pre‐operative DR, with male gender and with ethnicity …”
Section: Early Worsening Following Bariatric Surgerymentioning
confidence: 99%
“…Bariatric surgical procedures can cause prompt and sustained normoglycaemia in up to 80% patients with T2DM and episodes of postoperative reactive hypoglycaemia are not uncommon, making EW of DR a potential concern in this group . Retrospective studies have demonstrated variable effects of bariatric surgery on DR with worsening reported in between 1% and 45% of subjects 1 year after surgery . In a prospective observational study, 13% of patients exhibited progression of DR in the first 12 months post‐operatively, but only 5% of those persisted at 12 months .…”
Section: Discussionmentioning
confidence: 99%